How social media practices shape family business performance: The wine industry case study. Issue 3 (June 2022) - Obermayer, Nora; Kővári, Edit; Leinonen, Jaana; Bak, Gerda; Valeri, Marco
Abstract: The purpose of this paper is to investigate how family businesses utilise social media tools, to determine what the purposes, benefits and challenges are, and to discover competencies that are important in social networking and cooperation. A multiple case study method was employed based on semi-structured interviews with six wineries located in the Balaton region, Hungary. The interviewees and the wineries they represented were selected among the 55 wineries applying the non-probability sampling purposive technique and the interviews were analysed using a case study method and qualitative content analysis. The results show that Facebook is the most popular social media tool that wineries use to increase brand awareness and reach new potential customers. This study also presents a "Social media roadmap" framework for good practice and proposes practical steps family businesses may take to help them succeed in their marketing activities.